2013
DOI: 10.5603/cj.2013.0098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vascular age and classic cardiovascular risk factors and arterial stiffness

Abstract: (Cardiol J 2013; 20, 4: 394-401)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Providing CDS to patients is congruent with the current emphasis on patient‐centred care and shared decision‐making . From a practical point of view, giving CDS recommendations to patients presents many practical challenges, and evidence is slowly developing on the best way to present information on the risk and benefits of alternative treatment strategies to patients with varying degrees of numeracy and health literacy .…”
Section: Impact Of Cds On Diabetes Care Outcomesmentioning
confidence: 99%
“…Providing CDS to patients is congruent with the current emphasis on patient‐centred care and shared decision‐making . From a practical point of view, giving CDS recommendations to patients presents many practical challenges, and evidence is slowly developing on the best way to present information on the risk and benefits of alternative treatment strategies to patients with varying degrees of numeracy and health literacy .…”
Section: Impact Of Cds On Diabetes Care Outcomesmentioning
confidence: 99%
“…Our study for the first time, reported the changes in vascular age as a result of combination therapy with dulaglutide and SGLT2i. Vascular age reflects the real atherosclerotic damage and is considered as a new variable in cardiovascular risk assessment [11,12]. This study demonstrated significant improvement in vascular age at the follow-up compared with baseline.…”
Section: Discussionmentioning
confidence: 59%
“…() have also shown that among traditional CV risk factors type 2 diabetes mellitus was a predictor of the outcome that VA exceeded CA at least 5 years. Furthermore, these authors also found that BMI was an additional marker for advanced VA, but only in female population (Łoboz‐Rudnicka et al ., ). Masson et al .…”
Section: Discussionmentioning
confidence: 93%
“…(), who established that the VA of a person is equal to the age of an individual with the same estimated CV risk, but whose risk factors are within normal range. This point of view introduced the idea: ‘a man is old as his arteries’ which recently has drawn a growing attention in the field of the CV risk assessment (Grundy, ; Rosen et al ., ; Stein, ; Nilsson, ; Łoboz‐Rudnicka et al ., ). Additionally, VA represents the CA adjusted for individual's atherosclerotic burden, thus leading to the fact that there may be a substantial difference between these two types of ages in one person.…”
Section: Introductionmentioning
confidence: 97%